Islamic Puritanism Movements in Indonesia as Transnational Movements - Baskara, Benny (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
Islamic puritanism movements are the movements compelling to return to the teachings of Quran and Sunnah, as the pure teachings of Islam and abandon even abolish other teachings outside the teachings of Quran and Sunnah. The movements of Islamic puritanism can be considered as transnational movements because they spread their teachings and ideologies, create organizations, networks, and provide financial supports across nations. This paper describes Islamic puritanism movements in Indonesia and their transnational connections. Some Islamic puritanism movements in Indonesia can be considered as part of Islamic transnational movements, in which most of the movements are centered in the Middle East. In Indonesia, Islamic puritanism movements firstly appeared in the beginning of the nineteenth century, called Padri movement in West Sumatra. It was then continued to the emergence of Islamic organizations in the twentieth century. Recently, Islamic puritanism movements in Indonesia mostly take form as Salafism-Wahabism movements.